Synthesis of Polysubstituted Naphthalenes by Iron-Catalyzed [2+2+2] Annulation of Grignard Reagents with Alkynes - Ilies, Laurean; Matsumoto, Arimasa; Kobayashi, Motoaki; Yoshikai, Naohiko; Nakamura, Eiichi (Synlett, 2012)
Iron catalyzes the oxidative [2+2+2] annulation of an arylmagnesium compound with two molecules of an internal alkyne via C–H bond activation at 0 °C to produce polysubstituted naphthalene.
Keywords: alkynes; annulation; C–H bond activation; iron; naphthalene